2016
DOI: 10.1111/jfd.12437
|View full text |Cite
|
Sign up to set email alerts
|

First case of hepatopancreatic necrosis disease in pond‐reared Chinese mitten crab, Eriocheir sinensis, associated with microsporidian

Abstract: An epidemic of hepatopancreatic necrosis disease (HPND) with a high mortality rate (40%-50%) recently occurred in the cultured Chinese mitten crab, Eriocheir sinensis, which is a very important economic crustacean species in China. Histology revealed infection by a microsporidian parasite within the cytoplasm of the epithelial cells of the hepatopancreas. Numerous discrete inclusions in the infected cells and presumably free parasite spores were also observed. By negative staining using electron microscopy, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 21 publications
5
60
0
Order By: Relevance
“…This approach is powerful, because it simultaneously evaluates both viral and bacterial communities, and even suspected pathogens from the Eukaryota domain. Considering that RNA viruses can associate with certain diseases in E. sinensis (Zhang et al, 2004; Zhang and Bonami, 2007, 2012; Shen et al, 2015), and microsporidia were found in crabs infected with HPND (Ding et al, 2016), we analyzed the meta-transcriptomes of hepatopancreata from crabs with and without HPND to identify potential pathogens from viruses, bacteria, and eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach is powerful, because it simultaneously evaluates both viral and bacterial communities, and even suspected pathogens from the Eukaryota domain. Considering that RNA viruses can associate with certain diseases in E. sinensis (Zhang et al, 2004; Zhang and Bonami, 2007, 2012; Shen et al, 2015), and microsporidia were found in crabs infected with HPND (Ding et al, 2016), we analyzed the meta-transcriptomes of hepatopancreata from crabs with and without HPND to identify potential pathogens from viruses, bacteria, and eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…However, these crabs are of little/no economic value, and they eventually die. A previous study reported that microsporidia were detected in the hepatopancreata of crabs infected with HPND (Ding et al, 2016). In addition, hepatopancreatic injury caused by environmental toxicants is believed to be one of the main causes of HPND.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Ding et al [3] reported that infection of microsporidian Hepatospora eriocheir was associated with HPND, but animal regression test was not carried out. Meta-transcriptomes of the hepatopancreata from crabs with and without HPND were used to explore the etiology of HPND, and found that there were no striking differences in viral and microsporidial communities in the hepatopancreata of diseased and healthy crabs, however there were significant changes in the bacterial community of diseased and healthy crabs, increase of bacteria belonging to Tenericutes and Actinobacteria phyla and decrease of bacteria belonging to the Bacteroidetes phylum in crabs with HPND was suggested to associate with HPND [4].…”
Section: Introductionmentioning
confidence: 99%
“…In both studies, the spores were described as ellipsoid, measuring ∼1·8 × 0·9 µm and containing seven to eight polar filaments. Recently, Ding et al (2016) have shown that not only is the pathogen infecting the Asian population of Chinese mitten crabs H. eriocheir, but also the infection is associated with an emerging disease condition causing significant proportions in aquaculture production of this species in China. In their original taxonomic paper, Stentiford et al (2011) also highlighted an unassigned microsporidian infecting the hepatopancreas of edible crabs, C. pagurus, and suggested at the time that this was also likely a member of the genus Hepatospora based upon high similarity with the partial SSU gene sequence from H. eriocheir.…”
Section: Discussionmentioning
confidence: 99%